Noncommunicable disease modeling and simulation as means of understanding childhood obesity and intervention effectiveness - Meghana Aruru; Saumyadipta Pyne (Wolters Kluwer Medknow Publications, 2018)
Lifestyle and dietary changes have led to rise in noncommunicable diseases such as diabetes, obesity, and cardiovascular disorders, accounting for increased mortality and morbidity in many parts of the world including developing countries. Obesity has doubled since 1980s and continues to be a growing problem of our times. Public health policies to address obesity are evolving in connection with dynamically changing human behaviors and complex interactions with the environment. However, designing and testing of new interventions are expensive and time-consuming. Computational simulations to model interventions offer useful tools to compare the effectiveness of potential interventions. In this article, we discuss a popular computational approach, agent-based modeling (ABM), to address the global challenge of childhood obesity through modeling of different interventions as described in the literature.